PENGARUH LATIHAN PASSING WALL TERHADAP KETEPATAN MENGUMPAN PADA ATLET SSB BATUKARANG USIA REMAJA 13-15 TAHUN TAHUN 2025 - Januardi; Julius Boy Nesra Basgimata Barus; Deasyi Natalia Sitepu (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to determine the effect of passing wall training on passingaccuracy among 13–15-year-old athletes of Batukarang Soccer School(SSB Batukarang). Passing accuracy is one of the fundamental technicalskills in football that plays a crucial role in maintaining ball possession,developing attacks, and improving teamwork. Preliminary observationsindicated that the athletes' passing accuracy was still below expectations,highlighting the need for an effective training method to improve this skill.This research employed a quasi-experimental method using a one-grouppre-test and post-test design. The participants consisted of 10 athletesselected through purposive sampling. The research instrument was thePassing Accuracy Test, which was administered before (pre-test) and after(post-test) the implementation of the passing wall training program. Datawere analyzed using descriptive statistics, the Shapiro–Wilk normality test,and the Paired Sample t-Test. The findings revealed that the mean pre-testscore of 70.3 increased to 86.1 in the post-test, indicating an improvementof 15.8 points. The normality test showed that both pre-test and post-testdata were normally distributed (Sig. = 0.172 and Sig. = 0.527, respectively).Furthermore, the Paired Sample t-Test demonstrated a significance value(Sig. 2-tailed) lower than 0.05, indicating a statistically significantimprovement after the treatment. Therefore, it can be concluded thatpassing wall training has a significant positive effect on improving passingaccuracy among 13–15-year-old athletes of SSB Batukarang. This trainingmethod is recommended as an effective technical training strategy fordeveloping passing skills in youth football players.